IMF Staff papers, Volume 46 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1999)
This paper analyzes the predictability of currency crises. The paper evaluates three models for predicting currency crises that were proposed before 1997. Two of the models failed to provide useful forecasts. One model provides forecasts that are somewhat informative though still not reliable. Plausible modifications to this model improve its performance, providing some hope that future models may do better. The study suggests, though, that although forecasting models may help indicate vulnerability to crises, the predictive power of even the best of them may be limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet